Role Customer Satisfaction in Mediating Influence Product Quality and Attractiveness of Alternatives on Customer Recommendations (Studi at Saba Indomedika, Pontianak) - Iqbal, Muhammad; Heriyadi, Heriyadi; Barkah, Barkah; Ramadania, Ramadania; Juniwati, Juniwati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The aim of this research is to determine the influence of product quality and attractiveness of alternatives on word of mouth given by customers through the role of customer satisfaction as a mediating variable. Saba Indomedika faces challenges in maintaining product and service quality amidst intense competition. In this research, the population was 95 devices and the sample was 150 respondents from Saba Indomedika customers in West Kalimantan. To determine the research sample, a purposive sampling method was used. The data was processed using SmartPLS software version 4. This research found that there was a significant influence of product quality on customer satisfaction, then there was also an insignificant influence of the attractiveness of alternatives which influenced customer satisfaction, there was a significant and positive influence of product quality on customer recommendations. , there is an influence but not significant from the attractiveness of alternatives on customer recommendations, there is a significant influence from customer satisfaction on customer recommendations, then there is the role of customer satisfaction in indirectly influencing product quality on customer recommendations which is significant, on the contrary the research results reveal that there is no influence attractiveness of alternative to customer satisfaction and customer recommendations.